The inferior approach in hernia repair crural. Plasty of the crural septum by flap Greater oblique aponeurotic - Liard, Washington; Portos, Ruben; Valls, Alberto (Cirugía del Uruguay, 1972)
The use of the lower (femoral) approach in the treatment of femoral hernia is discussed and the most common technics are reviewed. The anatomic basis of the femoral approach are considered a new technic is proposed that basically consists in the rotation of an aponeurotic flap of the external oblique sutured to Cooper's Iigament therefore closing the internal aspect of femoral passage.